The Influence of Infaq and Shodaqoh Fundraising on Donors’ Satisfaction at Lazis MD UIN Jakarta - Sabela, Arifah Putri; Ibnugraha, Muhammad Ilgham; Hamdi, Muhammad Samman; Zaman, Ahmad Munawaru (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The fundraising activity conducted by LAZIS MD (Laboratory of Amil Zakat Infaq Shodaqoh of Da’wah Management) was a learning medium carried out by UIN Jakarta students in the Da’wah Management study program, Faculty of Da’wah and Communication Sciences in the Fundraising Management course. It was different from zakat institutions that are official and recognized by zakat institutions in Indonesia. It was called a laboratory because it was a learning medium, not an official institution and was not included in the category of fraudulent institutions. The problem in this laboratory was whether it had given satisfaction to the donors in terms of service, management, and the system. From the issues above, it could be emphasized that the formulation of the main problem in this research was how was the influence of infaq shodaqoh fundraising on donor satisfaction at LAZIS MD UIN JAKARTA? The purpose of this research was to find out if the program could be achieved adequately, could increase donors, and increase donors’ satisfaction. As an analytical tool, this study used a descriptive quantitative method, using a purposive sampling technique, in which the researcher took samples from all donors of LAZIS MD UIN Jakarta who matched their characteristics (100 people). The research instrument used a Likert Scale, to measure attitudes and opinions. The data collection technique used in this study was by filling out a questionnaire. This research provided an answer that donors were satisfied with the fundraising of infaq and shodaqoh carried out by LAZIS MD UIN JAKARTA. It could be proven by obtaining a score of 88.33% which of the 100 people who filled out the questionnaire, there were 75 people who chose the satisfied category.